Analisa Kasus Jaksa Farizal yang Menerima Suap Dana - Hartono, Ernita Dewy; Louissa, Natasha; sinsdanendra, Septyan; arrifa, Reisa; Roynita, Windy (Jurnal Ilmiah Wahana Pendidikan, 2023)
The rise of corruption cases that occurred became a driving force for the author to conduct research on this case. By using normative juridical writing techniques, namely collecting secondary materials and also literature study. From the results of the research, bribery of funds itself is an act of giving money or receiving money or gifts carried out by government officials to do or not doing something that’s contrary to their obligations, In Indonesia itself, cases of bribery often occur, even though this action violates Law No. 20 of 2001. The case presented by the author with this article is the case of Attorney Farizal receiving a bribe of 440, but Prosecutor Farizal has been sentenced by the court to a fine of 250,000,000 and imprisonment for 5 years. It could be nice for us to be aware of the case bribes around us.